1984
DOI: 10.1029/tc003i007p00759
|View full text |Cite
|
Sign up to set email alerts
|

Middle to Late Jurassic tectonic evolution of the Klamath Mountains, California‐Oregon

Abstract: The geochronology, stratigraphy, and spatial relationships of Middle and Late Jurassic terranes of the Klamath Mountains strongly suggest that they were formed in a single westfacing magmatic arc built upon older accreted terranes. A Middle Jurassic arc complex is represented by the volcanic rocks of the western Hayfork terrane and consanguineous dioritic to peridotJtic plutons. New U/Pb zircon dates indicate that the Middle Jurassic plutonJc belt was active from 159 to 174 Ma and is much more extensive than p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
119
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(124 citation statements)
references
References 26 publications
2
119
0
Order By: Relevance
“…3H) (Schweickert and Cowan, 1975;Ingersoll and Schweickert, 1986). No such collision occurred to the north in the Klamath Mountains, where the Klamath phase of the Nevadan orogeny involved opening and closing of a backarc basin behind the conti nental-margin arc concurrently with collision in the study area (Harper and Wright, 1984;Ingersoll and Schweickert, 1986). As the arcarc collision progressed, a new subduction zone began in what was the backarc of the intra oceanic arc (Fig.…”
Section: Late Jurassic Nevadan Orogenymentioning
confidence: 91%
“…3H) (Schweickert and Cowan, 1975;Ingersoll and Schweickert, 1986). No such collision occurred to the north in the Klamath Mountains, where the Klamath phase of the Nevadan orogeny involved opening and closing of a backarc basin behind the conti nental-margin arc concurrently with collision in the study area (Harper and Wright, 1984;Ingersoll and Schweickert, 1986). As the arcarc collision progressed, a new subduction zone began in what was the backarc of the intra oceanic arc (Fig.…”
Section: Late Jurassic Nevadan Orogenymentioning
confidence: 91%
“…The northern exposures of the imbricated BCA-Josephine Ophiolite-Rogue-Galice tectonic package represent collapse of the back-arc basin and its imbrication Tables 3 and 4. with the Chetco Arc. Harper & Wright (1985) have suggested that the Josephine Ophiolite represents oceanic crust formed in a Late Jurassic back arc where overlying flysch (Galice Formation) and volcaniclastic rocks (Rogue Formation) represent back-arc basin deposits (Riley 1987), and the Chetco Complex is the exposed roots of the arc forming the western 273 margin of the back-arc basin. Klippe of related amphibolites tectonically transported to the west in the Dothan Formationsuch as the Big Craggies, Game Lake, Red Mountain, and Gold Beach-are considered to be analogous to the BCA (Fig.…”
Section: Geologic and Tectonic Settingmentioning
confidence: 99%
“…It represents a complete ophiolite sequence overlain by silicic metasediments, the Galice Formation (Harper, 1984). The ophiolite has been dated at 157 ± 2 Ma and 164 ± 1 Ma (Saleeby et al, 1982;Wright and Wyld, 1986), and likely formed in a back-arc basin (e.g., Harper, 1980;Harper and Wright, 1984). The Josephine ophiolite and overlying Galice Formation were thrust eastward beneath the Klamath Mountains during the Nevadan orogeny, approximately 10 my after ophiolite formation.…”
Section: Geological Setting and Samplesmentioning
confidence: 99%